1998
DOI: 10.1191/096120398678920190
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenic properties of antiphospholipid antibodies do not depend on their binding to β2 glycoprotein 1 (β2GP1) alone

Abstract: Immunization of mice with beta2glycoprotein 1 (beta2GP1) induces production of antiphospholipid (aPL) antibodies, which were shown to have thrombus enhancing properties in an experimental mouse model, indicating that these antibodies are thrombogenic in vivo. To determine whether the thrombogenic effect of murine antiphospholipid antibodies is due to their aPL or their anti-beta2GP1 activity, we injected mice with murine monoclonal anticardiolipin (aCL) and anti-beta2GP1 antibodies. Effects of these antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…These antibodies had characteristics similar to those of the autoimmune human aPL, and their binding to PL was enhanced by addition of ␤ 2 GPI (13). These findings were reproduced by other investigators (14,15), and ␤ 2 GPI-induced aPL were shown to be pathogenic in certain strains of mice (16)(17)(18)(19).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…These antibodies had characteristics similar to those of the autoimmune human aPL, and their binding to PL was enhanced by addition of ␤ 2 GPI (13). These findings were reproduced by other investigators (14,15), and ␤ 2 GPI-induced aPL were shown to be pathogenic in certain strains of mice (16)(17)(18)(19).…”
supporting
confidence: 71%
“…␤ 2 GPI-induced aPL have been shown to be pathogenic in certain strains of mice, causing intrauterine fetal death, thrombocytopenia, and thrombosis (15)(16)(17)(18)(19). Induction of aPL is not dependent on immunization with the whole ␤ 2 GPI molecule.…”
Section: Discussionmentioning
confidence: 99%
“…This monoclonal Ab was shown to be thrombogenic and to activate ECs in previous studies. 40 Thrombus size was significantly larger in A2 ϩ/ϩ mice injected with 4C5 compared with same type of mice injected with MuMoAbC (P ϭ .002) or with anti-A2 MoAb (P ϭ .017; Figure 4B). The thrombogenic effects of 4C5 were significantly diminished in A2 Ϫ/Ϫ mice (P ϭ .005).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…40 The 4C5 was shown to bind to cardiolipin in a ␤ 2 GPI-dependent fashion, to have lupus anticoagulant and thrombogenic activity, and to activate ECs in previous studies. 40 The purified IgG was dialyzed against Tris-buffered saline, and the concentration of the protein was determined by the Bradford method. 39 A murine anti-A2 monoclonal Ab (anti-A2 MoAb) was used in some experiments (clone 5; BD Biosciences).…”
Section: Methods Preparation Of Immunoglobulin Gmentioning
confidence: 99%
“…Gharavi et al in 1999 synthesized a 15 amino acid peptide, GDKV, which spanned an area of the fifth domain of  2 GPI known to be a major PL-binding site of the molecule, and demonstrated the peptide's ability to induce pathogenic aPL and anti- 2 GPI antibody production in mice [48]. A monoclonal antibody with aPL and anti- 2 GPI activity generated from these GDKVimmunized mice was shown to be pathogenic using in vivo models for thrombus enhancement and microcirculation [49]. The resulting search for candidate peptides in microorganisms that exhibited functional and sequence similarity to the PL-binding domain of  2 GPI produced the peptides TIFI and VITT from cytomegalovirus (CMV), TADL from adenovirus (AdV) and SGDF from Bacillus subtilis.…”
Section: Origins Of Aps: Infection-associated Aps and Molecular Mimicrymentioning
confidence: 99%